The role of technology in interaction with the audience in digital art - Bagheri Lori, Mohammad Reza; Asghar Kafshchian Moghaddam, Nader Shayegan Far (Opción, 2019)
The present paper examines the role of technology in the production of work of art; and the impact on the audience in digital-oriented works with the aim to study the interaction of the audience and the digital effect based on the assumption that technology only raised the appearance of artistic forms into the problem. Examining the studies and available evidence by descriptive-analytical method, the results indicate that digital world has brought a new identity and new characters that have different psychology. In this situation, the artist and audience are present in a continuous interaction and are constantly converging.